DEVELOPING PROFESSIONAL COMPETENCE OF QUALIFIED WORKERS THROUGH COURSE TRAIN-ING IN ENTERPRISE SERVICE SECTOR TRAINING CENTERS - Boichuk, Vitaliy; Boichuk, Oksana (Professional Pedagogics, 2023)
Relevance: The article is driven by the need to develop professional competence in future skilled service sector workers through course training in training centers of service sector enterprises. The aim of the article is to identify general trends in the formation of professional competence of future skilled service sector workers in the process of course training in training centers of service sector enterprises. Methods: Study of scientific sources, legislative, normative-legal documents, empirical data – to identify general trends in the formation of professional competence of future skilled service sector workers in the process of course training in training centers of service sector enterprises. Results: Based on the analysis of modern legislative, normative-legal documents, research of scientific sources, and empirical data, the general trends in the formation of professional competence of future skilled service sector workers in the process of course training in training centers of service sector enterprises have been identified. Conclusions: The formation of professional competence in skilled workers during course training in training centers of service sector enterprises is a relevant process under martial law conditions, where due to migration processes, mobilization, and demographic problems in the country, there is an acute need for professional training and retraining of skilled personnel over short periods; this process faces several difficulties related to the reduction of production, financial and economic instability in the country, and insufficient development of flexible educational programs for short-term training and acquisition of partial professional qualifications.